THE USE OF TECHNOLOGY IN ENGLISH TEACHING & LEARNING PROCESS - Prayudi, Rizky Andra; Hakiki, Achmad Karunia; Putra, Nanda Rezki Dermawan; Anzka, Tio Ocatviano; Ihsan, Muhammad Taufik (Jurnal Riset dan Inovasi Pembelajaran, 2021)
This article is made to meet teacher teaching needs in using technology, especially in social media. For now, we are faced with Pandemic Covid-19 and also teachers continue to be demanded to be more careful in choosing the right technology when teaching online. This type of research is the method library research.This article is literature based in which the data and information were gathered from the book, internet postings, journal, etc. Technology includes the use of materials, tools, techniques and sources of power to make life easier . In education , Technology are really able to improve the teaching and leraning process.